2020
DOI: 10.1038/s41598-020-69963-3
|View full text |Cite
|
Sign up to set email alerts
|

Natural rubber as a renewable carbon source for mesoporous carbon/silica nanocomposites

Abstract: This study is the first report on the preparation of mesoporous carbon/silica (MCS) nanocomposites with tunable mesoporosity and hydrophobicity using natural rubber (NR) as a renewable and cheap carbon source. A series of mesoporous nanocomposites based on NR and hexagonal mesoporous silica (HMS) were prepared via an in situ sol-gel process and used as precursors; then, they were converted into MCS materials by controlled carbonization. The NR/HMS precursors exhibited a high dispersion of rubber phase incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…The so-called hard template in this synthesis strategy plays a similar role as molds in metal casting. Silica, [46][47][48][49][50][51] polymer beads, [52][53][54][55][56] metal oxide [57][58][59][60] and zeolite [61][62][63] are the most widely used templates. A typical hard template assisting synthesis process usually involves the following steps: as presented in Figure 2a, mesoporous solid phases or colloidal crystals are first prepared as sacrificial molds.…”
Section: Hard Template Based Methodsmentioning
confidence: 99%
“…The so-called hard template in this synthesis strategy plays a similar role as molds in metal casting. Silica, [46][47][48][49][50][51] polymer beads, [52][53][54][55][56] metal oxide [57][58][59][60] and zeolite [61][62][63] are the most widely used templates. A typical hard template assisting synthesis process usually involves the following steps: as presented in Figure 2a, mesoporous solid phases or colloidal crystals are first prepared as sacrificial molds.…”
Section: Hard Template Based Methodsmentioning
confidence: 99%
“…The N2 physisorption isotherms revealed the mesoporous character of these materials (Figure 1B), according to the IUPAC classification. Compared to the pristine HMS, the mesoporosity of NR/HMS and MCS was relatively lower (Table 1) due to the presence of organic moieties dispersed in the mesostructure framework [23]. The XRD patterns of the Nb/HMS and Nb/MCS with different Nb loading amounts are shown in Figure 2A,B, respectively.…”
Section: Physicochemical Properties Of Nb/hms and Nb/mcs Catalystsmentioning
confidence: 99%
“…Moreover, the humins yield was insignificantly changed. Nb2O5 is an acidic oxide with excellent hydrothermal stability in the aqueous-phase reaction systems [11][12][13].The carbon moieties dispersed in the MCS nanocomposites offered hydrophobic properties [23], and so retarded the adsorption of H2O on the catalyst surface. The overall results indicated that 10-Nb/MCS not only had good catalytic activity, but also high hydrothermal stability, in the selective synthesis of HMF from an aqueous glucose solution.…”
Section: Catalyst Reusabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Ceramic NPs (CNs) have emerged as drug delivery vehicles [ 46 ]. Silica nanoparticles (SNPs), discovered in 1992 by Kresge et al [ 47 ], are known to have superior textual properties, such as a high surface area, narrow pore size distribution, large pore volume, and tunable pore diameter, for disease diagnosis and cancer imaging [ 48 ]. Recently, Yuan et al [ 49 ] reported that SNPs encapsulating doxorubicin exerted antitumor effects through a burst release at an early stage and sustained release at a later stage.…”
Section: Recent Advances In Nanotechnology Targeting Cancer Progrementioning
confidence: 99%